2019
DOI: 10.5032/jae.2019.04115
|View full text |Cite
|
Sign up to set email alerts
|

Why Do They Leave and Where Do They Go? A Qualitative Study of Illinois School-Based Agriculture Teachers Who Left The Profession

Abstract: Approximately half of a million educators move or leave the profession each year with an estimated 41% of all educators exiting within the first five years. Additionally, agriculture teacher preparation programs are not producing enough graduates to meet current demands with 1,476 agricultural teacher vacancies existing in 2016 and only 772 individuals completing an approved teacher preparation program to become fully licensed. While the lack of young people entering the teaching profession is concerning, rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Some SBAE teachers leave teaching for other positions because of factors associated with compensation, such as salary, health benefits, retirement plans, and extended contracts . Feelings associated with adequate and fair compensation have been shown to be an important factor associated with teacher retention (Boone & Boone, 2009;Johnson & Birkeland, 2003;Lemons et al, 2015;Solomonson et al, 2019). Ingersoll and Smith (2003) found more than three-quarters of teachers sampled who left the profession were dissatisfied with their salary.…”
Section: Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some SBAE teachers leave teaching for other positions because of factors associated with compensation, such as salary, health benefits, retirement plans, and extended contracts . Feelings associated with adequate and fair compensation have been shown to be an important factor associated with teacher retention (Boone & Boone, 2009;Johnson & Birkeland, 2003;Lemons et al, 2015;Solomonson et al, 2019). Ingersoll and Smith (2003) found more than three-quarters of teachers sampled who left the profession were dissatisfied with their salary.…”
Section: Compensationmentioning
confidence: 99%
“…Many efforts have been made to identify factors leading to teacher attrition within SBAE (Blackburn & Robinson, 2008;Blackburn et al, 2017;Boone & Boone 2007;Boone & Boone 2009;Castillo & Cano, 1999;Chenevey et al, 2008;Croom, 2003;Hainline et al, 2015;Hasselquist et al, 2017;Kelsey, 2006;Kitchel et al, 2012;Knobloch & Whittington, 2003;Lambert et al, 2011;Lemons et al, 2015;McKim & Valez, 2015;Mundt & Conners, 1999;Murray et al, 2011;Myers et al, 2005;Solomonson et al, 2019;Sorenson et al, 2016a;Sorenson et al, 2016b;Tippens et al, 2013;Walker et al, 2004;Wolf, 2011). However, few studies have focused on teacher retention and why SBAE teachers remain in their current professions (Clark et al, 2014;Crutchfield et al, 2013, Rice et al, 2011, Thobega & Miller, 2003Warnick et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has identified unrealistic expectations, a lack of work-life balance, and an unattainable drive for success as a cause of teacher attrition and career dissatisfaction (Lemons et al, 2015;Solomonson et al, 2019;Traini et al, 2019) and has called for research to identify ways to shift the current paradigm and/or system of agricultural education profession to be more balanced (Lemons et al, 2015;Solomonson et al, 2019;Traini et al, 2019). A reimagination of how the three-component model, and specifically SAE, is conceptualized in agricultural education could address some of the systemic contributors to teacher attrition.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…At the school level, instability may take the form of teacher attrition, evidenced by teachers leaving the profession, or teacher mobility, manifested by teachers moving to a different school (Palma-Vasquez et al, 2022). leave (Igo & Perry, 2019;Lemons et al, 2015;Solomonson & Retallick, 2018;Solomonson et al, 2019;Solomonson et al, 2021;Solomonson et al, 2022;Sorensen et al, 2016). Within SBAE, licensed teachers made up approximately 85% of 1680 new hires nationwide in 2021 (Smith et al, 2022).…”
Section: Introductionmentioning
confidence: 99%